PENGARUH MODERNISASI PERTANIAN TERHADAP MORAL EKONOMI DAN ETIKA SUBSISTENSI PETANI PADI SAWAH DI DESA KARANG ANYAR KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Murniati, Ktut; Viantimala, Begem (Indonesian Journal of Socio Economics)
This research had done for, aim to know : influence agriculture modernization to economic moral and ethics subsitensi, change of social institute and the economic moral and also ethics of subsitensi at some social stratification socialize of rice field famer. This research location had been done at Countryside of Karang Anyar Subdistrict Gedong Tataan Regency Pesawaran. This research started from Juli 2006 until the December 2006. Research method used in this research is partisipative perception method and the circumstantial interview. Data analysis using descriptively qualitative that is elaborate or describe existing condition in research region manifestly through breakdown of words and also through tabulation. Others analyse data also use method analyse data reduction, data display and data selection. Analyse data started since process of data collecting until the obtaining conclusion of obtained data is known by the researcher.Â  Result of this research obtained that modernization in the field of agriculture specially the paddy, have had an effect on economic moral change and ethics subsistensi rice field paddy farmer, economic moral circumstance of farmer at Countryside of Karang Anyar before existence modernize, economics moral that grow is farmer feel yield up the production of paddy though not yet high, but its earnings last for fulfilling his requirement for that moment, while now, after existence modernize agriculture though produce paddy mount, its earnings cannot answer the demand requirement live in this time. Ethics of subsistensi that grow at society of rice field farmer show change of pattern of ethics subsistensi which is initially depending to "wholesaler" (pengijon) that happened at member of farmer group, in this time the pattern expand and emerge pattern "jimpitan", "borrow belong another of group member", and pattern "resiprositas" (exchange) of both for going together crop planted and also the requirement live of the other. Modernize agriculture that happen to this research location also cause the happening of change to social institute of rice field farmer at countryside karang anyar such as appearance of farmer group, P3A, "Jimpitan", and " rice gathering" in order to overcoming gristle subsistensi.